The first six-month clinical outcomes and risk factors associated with high on-treatment platelet reactivity of clopidogrel in patients undergoing coronary interventions - Tekkeşin, Ahmet İlker (Anatol J Cardiol, 2016)
OBJECTIVE: This study attempted to fill the gaps in evidence related to response to clopidogrel treatment in the Turkish population. The study aimed to determine the prevalence, associated risk factors, and clinical outcomes of high on-treatment platelet reactivity (HTPR) of clopidogrel in patients undergoing percutaneous coronary intervention (PCI) in a tertiary cardiovascular hospital in Turkey. METHODS: In this prospective studied a total of 1.238 patients undergoing PCI were included in the present study. Blood samples were analyzed using a Multiplate analyzer. All patients were examined in the outpatient clinics at the end of the first and sixth months for recording drug therapy compliance and study endpoints. RESULTS: Among the study population, 324 (30.2%) patients were found to have HTPR (mean age 58.03±11.88 years, 71.7% men). The incidence of HTPR was higher amongst females than amongst males (38.3% vs. 27%, p=0.010). Hypertension and diabetes mellitus were more frequently observed in the HTPR group (57.7% vs. 48.7%, p=0.004; 35% vs. 29.1%, p=0.040, respectively). When the recorded data were analyzed using multinomial regression analysis, hypertension, hemoglobin level, platelet, lymphocyte, and eosinophil count were independently associated with HTPR. CONCLUSION: On the basis of the results obtained from our study, we conclude that 30.2% of the Turkish population has HTPR. Our results also led us to believe that hypertension is an associated risk factor and decreased hemoglobin level as well as increased platelet counts are laboratory parameters that are strongly associated with the presence of HTPR. However, no differences were observed with regard to cardiovascular mortality and stent thrombosis. (Anatol J Cardiol 2016; 16: 967-73)